If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3k = -21 Solving 6 + -3k = -21 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -3k = -21 + -6 Combine like terms: 6 + -6 = 0 0 + -3k = -21 + -6 -3k = -21 + -6 Combine like terms: -21 + -6 = -27 -3k = -27 Divide each side by '-3'. k = 9 Simplifying k = 9
| -n+5=49.7 | | 12+r=14 | | S+2=2s+1 | | 9k-6=-429.9 | | 87=5n-13 | | 3.2c+8.7=84.54 | | -4x-6(5x-13)=-126 | | -4.5c=225 | | 3(4)2x+5=32 | | -8.4r=262.08 | | y-0.7=47.8 | | a+8.2=52.3 | | 6d-9=-147 | | 2r+4=4r | | 9*c=837 | | 4x=12x-4 | | 3y+15=51 | | 7c-5=131 | | -5(x-2)-9x=9(x-4) | | 158+2h=1004 | | 9n-4=-454 | | 158+2h=1008 | | 7(x+8)=5x | | .45=2/3x | | x+17=46 | | 4y=8x+43 | | 6x-19+3x+10=180 | | -8+4m+2m+4=2(m-8)-5(m+12) | | Sen^34x+1=0 | | 1-7c+2=16 | | 2q+386=872 | | (x+1)[x-(4-7i)][x-(4+7i)]=0 |